أثر استخدام الخرائط المعرفية في تنمية مهارة كتابة الهمزة المتوسطة لدى طلاب الصف الثالث المتوسط (The effects of using cognitive mapping in developing the skill of writing the middle hamza among students of third year secondary school) - (Adel Mohammed bin Suleiman Al-Muhanna), عادل بن سليمان محمد ال (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: هدفت هذه الدراسة إلى معرفة أثر استخدام الخرائط المعرفية في تنمية مهارة كتابة الهمزة المتوسطة والاحتفاظ بها لدى طلاب الصف الثالث المتوسط. وقد تكونت عينة الدراسة من (30) طالبًا من طلاب مدرسة عبدالله بن رواحة المتوسطة بمحافظة عنيزة المنتظمين في الفصل الدراسي الأول للعام الدراسي. وقد سار البحث وفقًا للمنهج التجريبي، حيث تم إعداد خرائط معرفية في موضوعات الهمزة المتوسطة للصف الثالث المتوسط، وكذلك إعداد اختبار تحصيلي مكون من (34) فقرة في صورته النهائية، يهدف إلى قياس المستويات المعرفية الأولى: (التذكر، الفهم، التطبيق)، ثم طبق قبليًا وبعديًا (عاجلاً ومؤجلاً) على مجموعتي الدراسة التي استغرقت (12) أسبوعًا. وقد أظهرت نتائج التحليل الإحصائي للفروق بين متوسطات درجات مجموعتي الدراسة باستخدام الاختبار التائي (T.Test) ما يأتي: تفوق المجموعة التجريبية على المجموعة الضابطة وذلك في اختبار التحصيل البعدي العاجل عند مستويات (التذكر، الفهم، التطبيق) مجتمعة ومنفصلة؛ وتفوق المجموعة التجريبية على المجموعة الضابطة وذلك في اختبار التحصيل البعدي المؤجل عند مستويات (التذكر، والفهم، والتطبيق) مجتمعة ومنفصلة، وهناك تأثير كبير لاستخدام الخرائط المعرفية كمنظم متأخر على تقليل الأخطاء الإملائية وعلى بقاء أثر التعلم لدى المجموعة التجريبية مقارنة بالمجموعة الضابطة. الكلمات المفتاحية: الخرائط المعرفية- الإملاء- كتابة الهمزة المتوسطة- مهارات الكتابة العربية-التطبيق. Abstract: This study aims to uncover the effects of using cognitive mapping in developing the skill of writing the middle hamza and preserving it among students of third year secondary school. The sample consists of 30 students from ‘Abdullah bin Rawwahah school in the District of ‘Unayzah during their first semester. The study is experimental; the cognitive map for learning the letter was prepared accordingly and the summative assessment consisting of 34 paragraphs were finalized. These were to measure the first level of knowledge (gender, understanding, application) which were applied before and after on two groups during the period of 12 weeks. The analysis of the findings revealed that the difference between the averages of marks from the groups though the use of T- test is as follows: the experimental group exceled over the control group in the assessment on the level of gender, understanding and application; the experimental group exceled over the control group in the deferred post-assessment in the levels of gender, understanding and application. Therefore, there is a strong correlation between the use of cognitive mapping and the process of learning the writing of hamza in the sample. Keywords: Cognitive mapping – spelling – writing of middle Hamza – Arabic writing skills - application Abstrak: Kajian ini bertujuan mengetahui kesan penggunan peta pengetahuan dalam penguasaan kemahiran menulis hamzah mutawassiţah dan mmengekalaknnya adlam pengetahuan pelajar tingkatan tiga. Respondan kajian terdiri daripada tiga puluh (30) orang pelajar Sekolah Menengah ‘Abdullah Bin Rawwāhah di wilayah ‘Unaizah pada Semester 1 bagi tahun pengajian. Kajian ini dijalankan dengan menggunakan metod eksperimental, di mana peta pengetahuan tentang hamzah mutawassiţah bagi tingkatam tiga serta ujian bertulis sebelum dan selepas telah dijalankan ke atas kedua buah kumpulan yang bertujuan mengukur tahap pembelajaran peringkat pertama (mengingat, memahami, mengaplikasi). Proses kajian telah mengambil masa 12 minggu. Dapatan statistik T-Test menunjukkan bahawa terdapat perbeazaan purata antara dua kumpulan dalam kajian di mana kumpulan kajian mengatasi kumpulan kawalan di dalam ujian selepas eksperimen. Ini menunjukkan bahawa terdapat implikasi besar dalam penggunaan peta pengetahuan sebagai faktor penyumbang ke arah pengurangan kesalahan ejaan serta sebagai faktor kelangsungan pembelajaran berkesan dalam kalangan kumpulan kajian berbanding dengan kumpulan kawalan. Kata kunci: Peta pengetahuan – Ejaan – penulisan hamzah mutawassiţah – kemahiran menulis dalam bahasa Arab – aplikasi.